Resenha do livro: Garcia, Tomás Fernandéz & Ponce de Léon Romero, Laura. (2019). Trabajo social individualizado: metodologia de intervención. Alianza Editorial. 448 p. : https://doi.org/10.53809/2021-01-TS-n.1-236-240 ("Temas Sociais" Journal, 2021)
Resenha do livro: Garcia, Tomás Fernandéz & Ponce de Léon Romero, Laura. (2019). Trabajo social individualizado: metodologia de intervención. Alianza Editorial. 448 p.